The Effect of Temperature and Storage Time on Chemical and Sensory Properties of Coconut Water Kefir - Liana, Sefira Putri; Jameelah, Maryam; Azis, Lukman (Green Engineering Society, 2024)
Coconut water kefir is a processed food product, derived from young coconut water. On this product, chemical and sensory properties are maintained through proper post-harvest handling. Therefore, this study aimed to determine the optimal temperature and storage time for coconut water kefir to produce the best sensory properties acceptable to the panelists. The effect of temperature and storage time treatments on chemical parameters was assessed through measurements of pH, °Brix, and alcohol content. Sensory analysis included both hedonic and hedonic quality testing. Furthermore, the experimental treatments applied were variations in storage temperature, both in the freezer (-25℃) and refrigerator (3℃), and storage time of 0, 1, 7, 14, and 21 days. The results showed that the interaction between temperature and storage time had no significant effect on the pH value and °Brix of coconut water kefir. All samples had low alcohol content, with values below 1%. The optimum sensory properties, as perceived by the panelists, were observed in the sample stored at a refrigerated temperature for 1 day. Further statistical analysis using the Kruskall-Wallis Test showed that refrigerator storage had a significant effect on hedonic and hedonic quality testing. Conversely, freezer storage had a significant effect on only the hedonic quality test.